Study of metabolic activity of human embryos focused on amino acids by capillary electrophoresis with light-emitting diode-induced fluorescence detection - Celá, Andrea; Mádr, Aleš; Ješeta, Michal; Žáková, Jana; Crha, Igor; Glatz, Zdeněk (Electrophoresis, 2018)
Assisted reproduction is a quickly developing field of reproductive medicine whose importance is growing every year due to the increasing number of patients suffering from infertility. As a result, there is a need for the continuous development and/or improvement of assisted reproductive technologies. This paper presents a new method for the in vitro measurement of the amino acid turnover of developing embryos based on capillary electrophoresis with light-emitting diode-induced fluorescence detection. Amino acids were derivatized with naphthalene-2,3-dicarboxaldehyde/NaCN, and the resulting fluorescent derivatives were baseline resolved within 25 min in a background electrolyte comprised of 50 mM sodium tetraborate, 73 mM sodium dodecyl sulphate, 5 mM sodium deoxycholate and 2.5 mM (2-hydroxypropyl)-β-cyclodextrin (pH ≈ 9.3). The migration time and the peak area repeatability (n = 10) were below 0.5 and 4.3%, respectively. The limits of detection ranged from 12.6 nM (histidine) to 39.3 nM (taurine). The developed method, which only requires 2 μL of raw sample, was successfully applied for determining the metabolic activity of human embryos exposed to different environmental stress conditions.
Keywords: Culture Media; naftaleny; Reproducibility of Results; asistovaná reprodukce; Humans; lidé; reprodukovatelnost výsledků; Amino Acids; Naphthalenes; Reproductive Techniques, Assisted; Electrophoresis, Capillary; kultivační média; aminokyseliny; embryo savčí; Embryo, Mammalian; Spectrometry, Fluorescence; elektroforéza kapilární; fluorescenční spektrometrie